PORTRAIT OF THE PALESTINIAN CITY IN QODIDAH "EXCEPT THOSE WHO DISOBEY" & QURBA MURBID NA'AMAH BY MUHAMMAD ABU DAUD - Asmu'i, Ali Mahmud (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study discusses the problem of a poet regarding the problems that occur in the city, to what extent he feels the suffering that afflicts the residents of the city. This city seems to be a symbol of existence, eternity & stagnation. How did events hit the city? Will he be able to take the pain out of the city and its citizens? Can he feel the suffering of the townspeople and make it part of his concern?